Turning Sustainability into Strategic Growth in Frontier Markets - Nguyen, Thi Ha; Nguyen, Thai Ha Thuong; Đinh, Le Hanh (Archives of Business Research, 2025)
In the scenario that frontier markets are currently facing up with pressure of rapidly growth but without sustainability, this paper offers an approach to sustainability growth, based on “Beyond Greening”, a sustainability strategy launched by Stuart L.Hart. Instead of considering environment protection as a compliance, the paper emphasizes that companies can take advantages of growing sustainable as a motivation to create long-term strategic values via three stages: Pollution Prevention, Product Stewardship, and Clean Technology. However, the results show that the pursuing sustainability strategies cannot be separated from governance reform, the readiness in investing in intrinsic capabilities to transit from compliance to value creation.